The Influence of Drill Defense Training on Improving Underhand Passing Skills in Volleyball at the Extracurricular Program Of SMA Negeri 1 Lebakwangi - Rahmawati, Senita; Fauzan, Elang (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to improve volleyball players' forearm passing skills through the implementation of drill defense training. The main issue addressed is the low effectiveness of players in receiving attacks from opponents, which negatively impacts the overall team performance. This research employed an experimental method with a one-group pre-test and post-test design using a quantitative approach. The subjects were female students participating in the volleyball extracurricular program at SMA Negeri 1 Lebakwangi, selected through purposive sampling. The Brady Volleyball test was used to assess forearm passing ability before and after the drill defense training. Data analysis was conducted using the Paired Samples T-Test, along with normality and homogeneity tests to ensure data validity. The results showed a statistically significant improvement with a significance value of p < 0.05. The data were normally distributed and homogeneous. Drill defense training proved effective in enhancing forearm passing skills and is recommended to be implemented regularly in training programs.